Limit of adhesion coefficient measurement of a unidirectional carbon fabric. (4th November 2015) - Aimé, Hugo; Comas-Cardona, Sébastien; Binetruy, Christophe; Schell, Julia; Lacrampe, Marie-France; Deléglise-Lagardère, Mylène
Abstract : The construction of mesoscopic models of fiber washing effects during the high pressure resin transfer molding (RTM) process with thermoplastic polymers requires the knowledge of the limit of adhesion coefficients between dry and impregnated fabric reinforcement plies and the mold. To measure these coefficients, a new method is described. During RTM process, a preform is placed in the cavity. The mold is closed to reach a given cavity thickness. Therefore, the normal stress applied to the preform can be relaxed before injection. In order to comply with these RTM specificities, the limit of adhesion coefficients are measured on relaxed preforms at given thicknesses. Hence, a first set of compression tests followed by a relaxation step are performed in order to measure the normal stresses the preforms undergo. The relaxation can reduce compression normal stress by 30%. The relaxation is taken into account for the limit of adhesion calculation. Then a second setup has been built in order to measure forces during pull-out of fabric plies inserted between other plies or metallic plates. This method provides mean values of coefficients of limit of adhesion for dry and lubricated preforms and various stacking sequences. These coefficients can be refined so as to take into account the real area of the contact interface for ply/ply and ply/mold configurations. There are also useful in the forming process of dry fabrics when inter-ply sliding occurs.